"Daltexpharma": A Case Addressing Potential Pharmaceutical Cargo Theft - Tiffany M. Marchione; Nile M. Khanfar; Bahaudin G. Mujtaba; David Loudon (University of Minnesota Libraries Publishing, 2020)
Case Synopsis This paper is provided as an innovative resource for those in the academic and training arenas to use as a case example in discussing the problem of pharmaceutical cargo theft.  The case delves into the worldwide, on-going dilemma of pharmaceutical trucking cargo theft losses and the effects of such theft.  For those unfamiliar with the case method of instruction, the paper's ending may be rather unsettling.  But that is where the student's learning and faculty instruction process come together.  Typically, students (whether in teams or individually) will fully develop their responses based on the queries provided at the end.  Faculty may then proceed in any number of ways to elicit the students' insights in a classroom setting.  For decades the pharmaceutical industry has been plagued with a plethora of criminal acts that impact the daily processes and procedures of operations.  Pharmaceutical warehouse and trucking thefts have not only aided in the currently debilitating state of the opioid crisis in the United States, but these thefts also aid the black market in the illegal sale of diverted prescription drugs.  Due to the lack of security measures, vulnerability of the truck drivers, their rigs, and the value of the cargo being transported, pharmaceutical theft is a lucrative opportunity for organized crime.  The case presented here describes the issues within the pharmaceutical industry as companies must deal with "last mile" cargo thefts.  Daltexpharma represents a synthesized, hypothetical example of a pharmaceutical firm that must develop policies to deal with such potential thefts in its supply chain.  Although a fictitious company, the case realistically details the important factors to consider in establishing strong security practices that may be necessary for a pharmaceutical company operating in today's environment.  In order to protect the integrity and security of the authors' case notes, particularly for use in an academic setting, the Journal's editor will maintain control of them.  They may be obtained by faculty upon presenting their request to the Editor.    Article Type: Instructional Tool